Linking relational coordination to nurses' job satisfaction, affective commitment and turnover intention in Saudi Arabia. (10th April 2019) - Falatah, Rawaih; Conway, Edel
Abstract: Aim: To examine the association between relational coordination, job satisfaction, affective commitment and turnover intention. Background: While there is a substantial body of literature that examines how relational coordination influences outcomes among nurses in western societies, there is no known study that examines the impact of relational coordination on outcomes in a non‐western health care system. As many of the factors associated with nursing turnover in Saudi Arabia are uniquely complex and challenging, a focus on relational coordination in this context is particularly worthy of investigation. Method: The study utilized a cross‐sectional online survey. A total of 180 nurses participated in the study. Results: The results indicated that the relationship between relational coordination and turnover intention is mediated by job satisfaction. The results further show that the relationship between relational coordination and turnover intention is mediated by affective commitment. Conclusion: High levels of relational coordination can give rise to various outcomes of relevance to nurses, allied health professionals and patients. Implications for Nursing Management: Reconfigured job designs to build and cultivate links between nurses and other clinical disciplines will be necessary to enhance job satisfaction and commitment levels and to reduce turnover intention.